2019
DOI: 10.1021/acs.langmuir.9b03025
|View full text |Cite
|
Sign up to set email alerts
|

Short and Soft: Multidomain Organization, Tunable Dynamics, and Jamming in Suspensions of Grafted Colloidal Cylinders with a Small Aspect Ratio

Abstract: The yet virtually unexplored class of soft colloidal rods with small aspect ratio is investigated and shown to exhibit a very rich phase and dynamic behavior, spanning from liquid to nearly melt state.Instead of nematic order, these short and soft nanocylinders alter their organization with increasing concentration from isotropic liquid with random orientation to one with preferred local orientation and eventually a multi-domain arrangement with local orientational order. The latter gives rise to a kinetically… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 86 publications
0
5
0
Order By: Relevance
“…In soft colloids or mixtures, a hybrid polymeric and colloidal rheological response can be typically detected, as in the case of previous star−linear polymer mixtures, 5 grafted nanoparticle melts, 36 or diblock copolymer micelles. 59 The polymeric and the colloidal responses are characterized by two different stress relaxation mechanisms that occur on different time scales and proceed hierarchically. At high frequencies, the response is dominated by the polymer matrix, and the plateau modulus reflects the polymeric network response, and is estimated by taking into account only the free volume accessible to the chains.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In soft colloids or mixtures, a hybrid polymeric and colloidal rheological response can be typically detected, as in the case of previous star−linear polymer mixtures, 5 grafted nanoparticle melts, 36 or diblock copolymer micelles. 59 The polymeric and the colloidal responses are characterized by two different stress relaxation mechanisms that occur on different time scales and proceed hierarchically. At high frequencies, the response is dominated by the polymer matrix, and the plateau modulus reflects the polymeric network response, and is estimated by taking into account only the free volume accessible to the chains.…”
Section: Resultsmentioning
confidence: 99%
“…In soft colloids or mixtures, a hybrid polymeric and colloidal rheological response can be typically detected, as in the case of previous star–linear polymer mixtures, grafted nanoparticle melts, or diblock copolymer micelles . The polymeric and the colloidal responses are characterized by two different stress relaxation mechanisms that occur on different time scales and proceed hierarchically.…”
Section: Resultsmentioning
confidence: 99%
“…Further details about these nanoparticles are reported elsewhere. 10,59 Table 1 reports the molecular characteristics of the spherical micelles used in the present work; core radius (Rc), polydispersity index (PD) of the polystyrene chains, number-average molar mass of the PS arm (Mn,arm), PS weight fraction respect to the total particle (PS fraction), grafting density (), aggregation number (Nagg), and the weight-average molar mass (Mw) of the whole nanoparticle calculated as Mw = (Mn,arm•PDI)/PS fraction.…”
Section: Methodsmentioning
confidence: 99%
“…Nematic fluids have always received a great deal of attention due to their rich opto-mechanical properties. A wide plethora of systems showing nematic phases have been investigated over the years, including rigid rods, fd viruses, , polymer-grafted nanocylinders, , and liquid-crystalline polymers. The isotropic–nematic (I–N) transition promoted by shear is not sharp for polydisperse systems, but it can involve phase coexistence on different length scales (domains). The resulting nematic phase, as in the case of liquid crystals subjected to shear, can be characterized by the nematic director fluctuation and the motion in the velocity direction, such as collective tumbling and wagging, or by the orientation in the vorticity direction but the motion in the velocity direction, such as log-rolling and kayaking. ,, These regimes are controlled by many factors, including the initial orientation of the system, polydispersity, interaction potential, aspect ratio, chain flexibility, domain composition, and shear rate. ,,, Whereas the I–N transition promoted by shear has been extensively investigated in polymeric or colloidal solutions, ,,,, much less is known about polymer melts. Most of the literature refers to thermotropic melts. ,,, Of considerable importance are the work of Beekmans et al, who confirmed the presence of fluctuations in the shear stress and first normal stress difference in transient shear experiments, the in situ X-ray scattering experiments of Rendon et al and Romo-Uribe and Windle, probing tumbling and log-rolling, respectively, and the work of Gotsis et al, investigating the shear-thinning regime of nematic melts with pressure-driven flows in capillary and slit dies.…”
mentioning
confidence: 99%
“…N ematic fluids have always received a great deal of attention due to their rich opto-mechanical properties. A wide plethora of systems showing nematic phases have been investigated over the years, including rigid rods, 1−3 fd viruses, 4,5 polymer-grafted nanocylinders, 6,7 and liquid-crystalline polymers. 8−11 The isotropic−nematic (I−N) transition promoted by shear is not sharp for polydisperse systems, but it can involve phase coexistence on different length scales (domains).…”
mentioning
confidence: 99%